1987
DOI: 10.1093/jnci/78.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Carcinogenesis: Effect of Secretin in the Hamster-Nitrosamine Model2

Abstract: The effect of exogenous secretin on pancreatic carcinogenesis in WO strain hamsters has been examined in the nitrosamine-ductular adenocarcinoma model. Secretin, 20 clinical U/kg, stimulated a maximal secretory response of pancreatic juice and bicarbonate when given iv. The same dose given sc for 6 weeks had no significant effect on pancreatic wet weight and DNA or RNA contents. However, when given to animals receiving N-nitrosobis(2-oxopropyl)amine [(BOP) CAS: 60599-38-4] (5 mg/kg), it reduced the latency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…It has been also proposed that the effects of food consumption patterns on pancreatic cancer risk may be mediated by gastrointestinal hormones. Choleocystokinine-pancreazymin (CCK) (201-203) and secretin (204) have been postulated to promote cellular proliferation and growth in the pancreas, and it is a commonly held view that increased proliferation may sensitize the pancreas to an accumulation of genetic modifications caused by other agents, of either exogenous or endogenous origin. Among the strongest stimulators of CCK release are digestion products of protein and fats (205).…”
Section: Discussionmentioning
confidence: 99%
“…It has been also proposed that the effects of food consumption patterns on pancreatic cancer risk may be mediated by gastrointestinal hormones. Choleocystokinine-pancreazymin (CCK) (201-203) and secretin (204) have been postulated to promote cellular proliferation and growth in the pancreas, and it is a commonly held view that increased proliferation may sensitize the pancreas to an accumulation of genetic modifications caused by other agents, of either exogenous or endogenous origin. Among the strongest stimulators of CCK release are digestion products of protein and fats (205).…”
Section: Discussionmentioning
confidence: 99%
“…These authors assume that the diet change causes a fall of plasma cholecystokinin, and the removal of the trophic stimulus of cholecystokinin is probably responsible for pancreatic involution (30,31). Other studies (32)(33)(34)(35) showed that cholecystokinin and other gastrointestinal hormones probably influence growth of the pancreatic malignant cells and the process of phenotypic transformations. Cerulein, which is structurally closely related to cholecystokinin, given together with secretin, stimulated the growth ofpancreatic ductal adenocarcinoma H-2-T in hamsters in vivo (33).…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of high dose phenylalanine significantly increased the basal serum gastrin level and significantly decreased the norepinephrine concentration in the antral portion of the gastric wall, as well as the labelling indices of antral mucosa. These findings indicate that orally administered phenylalanine inhibits the development of gastric cancers.Gastrointestinal regulatory peptides, such as vasoactive intestinal peptide (lishi et al, 1987), secretin (Howatson & Carter, 1987), cholecystokinin and its analogue (Satake et al, 1986), and gastrin (Tatsuta et al, 1977b), have been found to regulate development of cancers of the gastrointestinal tract and the pancreas. We recently found that prolonged alternate-day administration of the potent duodenal ulcerogen cysteamine after 25 weeks of N-methyl-N'-nitro-Nnitrosoguanidine (MNNG) treatment led to marked hypergastrinaemia and also to significant protection against the development of gastric cancers (Tatsuta et al, 1988a).…”
mentioning
confidence: 99%